POTENTIAL OF ANTHOCYANIN BASED POLY (METHYL METHACRYLATE) NANOPARTICLES SPECIFIC ACTIVATED MICROGLIA IN MANAGEMENT INFLAMMATORY PAIN ON HERNIATED NUCLEUS PULPOSUS: A LITERATURE REVIEW - Widyadharma, I Putu Eka; Satyarsa, Agung Bagus Sista; Sanjaya, Feliani; Gitari, Ni Made; Niryana, I Wayan; Purwata, Thomas Eko; Jawi, I Made; Suprapta, Dewa Ngurah; Sudewi, AA Raka (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Pain is an unpleasant sensory and emotional experience that can affect the quality of life and leads to decreased productivity in patients. Low back pain (LBP) is one of the significant causes of disability worldwide with lifelong incidence. The purpose of this literature review describes the potential of anthocyanin-based Poly (Methyl Methacrylate) (PMMA)Â Â nanoparticles as the management of inflammatory pain in the Hernia Nucleus Pulposus (HNP ). The method used is a literature study by entering the keyword. Of the 77 journals reviewed, 47 journals were found by the topic and used as a reference for this work. The anthocyanin-based PMMA nanoparticles act as anti-nociceptors by inhibiting microglia that produce inflammatory mediators in HNP. Poly (Methyl Methacrylate) nanoparticles have specific targets in microglia. Anthocyanins have the effect of inhibiting inflammatory pain through many destinations. Anthocyanin inhibits the synthesis of nitric oxide (NO ) and prostaglandin E2 (PGE 2) and inhibits the activation of p38 MAPK and NF-kB pathways that express TNF-Î± and IL-1Î² genes as anti-nociceptive. The anthocyanin-based PMMA nanoparticles have potential as a novel therapy for inflammatory pain in HNP. There has been no research between these modalities. Therefore, further research is needed to find out the exact potential of anthocyanin-based PMMA nanoparticles.